2013
DOI: 10.1136/bmj.f108
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal risk factors for stillbirth: population based study

Abstract: Objective To assess the main risk factors associated with stillbirth in a multiethnic English maternity population. Design Cohort study.Setting National Health Service region in England.Population 92 218 normally formed singletons including 389 stillbirths from 24 weeks of gestation, delivered during 2009-11.Main outcome measure Risk of stillbirth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
736
8
20

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 761 publications
(814 citation statements)
references
References 29 publications
(27 reference statements)
50
736
8
20
Order By: Relevance
“…Our data demonstrate that poor fetal growth and SGA at birth, particularly when not suspected during pregnancy, are asociated with antepartum stillbirth 9. However, this association was less evident in the subset of women with longitudinal ultrasound data, selected as they were, for low risk of growth problems.…”
Section: Discussionmentioning
confidence: 58%
“…Our data demonstrate that poor fetal growth and SGA at birth, particularly when not suspected during pregnancy, are asociated with antepartum stillbirth 9. However, this association was less evident in the subset of women with longitudinal ultrasound data, selected as they were, for low risk of growth problems.…”
Section: Discussionmentioning
confidence: 58%
“…We adjusted the risk of all outcomes of interest for maternal age, socioeconomic deprivation (Carstairs quintile), 15 parity, previous cesarean section, previous emergency admission, comorbidities (Charlson score), 16 multiple gestation, operations on amniotic cavity (including amniocentesis, sampling of chorionic villus), obstetric surgery, and for the presence of cardiac disease, hypertension/preeclampsia, and gestational diabetes [17][18][19][20][21][22][23][24] (Supplement Table 1, http://links.lww.com/SLA/B89).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that two thirds of stillbirths were traditionally considered unexplained, it was revealed that 43% of these fetuses were FGR using a different stillbirth post-mortem classification system [5]. Furthermore, a retrospective population study has shown that the antenatal detection of SGA could potentially halve the risk of stillbirth [6]. Therefore, improving the identification of the small for gestational age (SGA) fetuses potentially could prevent stillbirth, likely through appropriate antenatal surveillance and timely delivery [6][7][8][9].…”
Section: Highlightsmentioning
confidence: 99%
“…Furthermore, a retrospective population study has shown that the antenatal detection of SGA could potentially halve the risk of stillbirth [6]. Therefore, improving the identification of the small for gestational age (SGA) fetuses potentially could prevent stillbirth, likely through appropriate antenatal surveillance and timely delivery [6][7][8][9]. At present, the prenatal detection of SGA is achieved in only about 1 in 4 cases [6][7][8][9].…”
Section: Highlightsmentioning
confidence: 99%